HUKUM EKONOMI DAN BISNIS DI INDONESIA - Subaidi Subaidi (LP2M Universitas Ibrahimy, 2016)
Economic has developed the forms of electronic transactions with the advancement of technology. That is the form of commitment or legal relationship that becomes a trending topic as an online contract. Certainly, it is done by electronically networking of information system technology. E-commerce is the transaction that has been switched implementation, from an authorized signature in the paper as document transactions, into electronic transactions document without a paper and signature, so it is proof of the validity of the transaction. It is happens in the event of a legal corporate transplantation in the law institutions. In this case, the body is in the form of law while his feet still rests on the top of the law, which in many cases this transplant is applicable. As a result, has developed a new legal bussiness institutions that were not regulated previously in the Indonesian legal system, which in theÂ implementation often cause conflicts or disputes, which in this case is known as a commmercial disputes. Corporation or company is the important legal order, consider the fairly rapid business growth and also consider the case of disputes that require certainly and definitely of legal institution for the organization. Therefore, business law and corporate law is needed in practice.